Boraxs and Formalin Analysis in the Shumai Treated in Palu City - Areeya Milehman; Mery Napitupulu (Universitas Tadulako, 2020)
This study aims to test and prove the presence of borax and formalin contamination in shumai samples sold in Palu City. A qualitative method with curcumin paper test; and quantitatively using the UV-Vis spectrophotometer method on a 550 nm wavelength, so that the borax content can be determined in the sample. From the results of this study as many as 5 shumai samples examined, all samples from 5 samples tested qualitatively positive were found before the quantitative analysis was carried out before the samples were tested qualitatively. Qualitative tests showed that some samples did not contain formaldehyde but positively contained borax so the quantitative test was only conducted to determine borax levels in shumai. The results stated that the lowest level was 0.0213 mg/g and the highest level was 0.0314 mg/g.